EFEKTIFITAS THE HEART TECHNIQUE TERHADAP PENURUNAN KECEMASAN PADA IBU HAMIL - Lila Kusuma Rahayu; Widayati Widayati; Wahyu Kristiningrum (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2020)
ABSTRACT Background: The Heart Technique (THT) is a self-therapy technique that is performed on oneself and has been clinically tested to effectively deal with problems that are related to behavior and emotions. Every mother experiences symptoms of pregnancy - different, most pregnant women experience anxiety in dealing with their pregnancy. Pregnant women who experience high levels of anxiety can increase risk of preterm birth, besides pregnant women with high anxiety when pregnant will increase the risk of hypertension in pregnancy. The risk of hypertension can be in the form of stroke, seizures, and even death in the mother and fetus. If this is allowed to happen, the mortality and morbidity rates in pregnant women will increase. Purpose: to determine the effectiveness of The Heart Technique in reducing anxiety in pregnant women. Methods: This research was a quasi-experimental study. The treatment of THT was given to 17 pregnant women. Pregnancy anxiety is measured before and after pregnant women do THT. The data obtained were processed using a dependent t-test because the data were normally distributed. Results: Research that has been done shows that THT can reduce anxiety in pregnant women. This can be seen from the results of data processing obtained is the calculated value of -7.115 with a p value of 0,000 so the value is 0,000 <α (0.05). Conclusion: The Heart Technique is effective against Decreasing Anxiety in Pregnant Women in Langensari Village, Ungaran Barat, Semarang Regency. Suggestion: In providing pregnancy services, it is expected that health workers can provide additional information about The Heart Technique to pregnant women Keywords: The heart technique, pregnant women, anxiety ABSTRAK Latar belakang : The Heart Technique (THT) adalah teknik swaterapi yang dilakukan pada diri sendiri dan telah teruji klinis secara efektif untuk mengatasi masalah yang berhubungan dengan perilaku dan emosi. Adanya ibu hamil yang mengalami kecemasan dalam masa kehamilan, dimana yang nantinya dapat berpengaruh terhadap kondisi bayi yang dikandungnya. Ibu hamil yang mengalami kecemasan, maka bayi yang dikandungan juga akan mengalami kecemasan. Hal ini dikarenakan, apapun yang dirasakan oleh ibu, maka bayi yang ada didalam kandungan juga akan merasakannya. Tujuan : untuk mengetahui keefektifan The Heart Technique dalam menurunkan kecemasan pada ibu hamil. Metode : Penelitian yang dilakukan ini termasuk penelitian quasi eksperimen. Perlakuan THT diberikan pada ibu hamil yang berjumlah 17 orang. Kecemasan ibu hamil diukur sebelum dan sesudah ibu hamil melakukan THT. Data yang diperoleh diolah menggunakan uji dependent t-test karena datanya berdistribusi normal. Hasil : Penelitian yang sudah dilakukan menunjukkan bahwa THT dapat menurunkan angka kecemasan pada ibu hamil. Hal ini terlihat dari hasil pengolahan data yang didapatkan yaitu nilai t hitung sebesar -7,115 dengan nilai p sebesar 0,000, sehingga nilai 0,000 < α (0,05). Kesimpulan: The Heart Technique efektif terhadap Penurunan Kecemasan pada Ibu Hamil di Kelurahan Langensari Ungaran Barat Kabupaten Semarang. Saran : Dalam memberikan pelayanan kehamilan, diharapkan tenaga kesehatan dapat memberikan informasi tambahan tentang The Heart Technique pada bu hamil. Kata kunci : The heart technique, ibu hamil, kecemasan